Measurement of Budget Performance Value at The Secretariat of The Directorate General of Vocational Education - adi , Agung; Sari, Rida; Shufia Zuhroh (Journal of Financial and Behavioural Accounting, 2023)
Ministry/Institution Work Unit Budget Performance is an achievement of the results of performance that has been carried out by work units in Ministries/Institutions in work and budget planning and budget execution that has been carried out based on predetermined targets in budget documents with consideration of achievements on budget management and indicators budget performance in a one-year budget period. The Secretariat of the Directorate General of Vocational Education as one of the work units within the Ministry of Education, Culture, Research, and Technology has the main duties and functions in the form of service management support, one of which is in the field of budget management and financial implementation. The author conducted this research in order to find out the level of budget performance obtained by the Secretariat of the Directorate General of Vocational Education for the 2020 and 2021 fiscal years. The research method was carried out using a qualitative phenomenological approach which was analyzed descriptively. The data used are data on the value of the Budget Performance Evaluation (EKA) aspect and data on the value of the Budget Implementation Performance Indicator (IKPA) aspect. The results of the study show that within 2 (two) years, since it was formed, the Secretariat of the Directorate General of Vocational Education obtained a Budget Performance Score with a VERY GOOD predicate but has decreased from 2020 to 2021 so improvements are needed in several aspects of the existing indicator variables.